Effects of the (Pro)renin Receptor on Cardiac Remodeling and Function in a Rat Alcoholic Cardiomyopathy Model via the PRR-ERK1/2-NOX4 Pathway. (13th March 2019) - Cao, Xinran; Yu, Shiran; Wang, Yuanyuan; Yang, Min; Xiong, Jie; Yuan, Haitao; Dong, Bo
Abstract : Alcoholic cardiomyopathy (ACM) caused by alcohol consumption manifests mainly as by maladaptive myocardial function, which eventually leads to heart failure and causes serious public health problems. The (pro)renin receptor (PRR) is an important member of the local tissue renin-angiotensin system and plays a vital role in many cardiovascular diseases. However, the mechanism responsible for the effects of PRR on ACM remains unclear. The purpose of this study was to determine the role of PRR in myocardial fibrosis and the deterioration of cardiac function in alcoholic cardiomyopathy. Wistar rats were fed a liquid diet containing 9%v / v alcohol to establish an alcoholic cardiomyopathy model. Eight weeks later, rats were injected with1 × 10 9 v . g . / 100   μ l of recombinant adenovirus containing EGFP (scramble-shRNA), PRR, and PRR-shRNA via the tail vein. Cardiac function was assessed by echocardiography. Cardiac histopathology was measured by Masson's trichrome staining, immunohistochemical staining, and dihydroethidium staining. In addition, cardiac fibroblasts (CFs) were cultured to evaluate the effects of alcohol stimulation on the production of the extracellular matrix and their underlying mechanisms. Our results indicated that overexpression of PRR in rats with alcoholic cardiomyopathy exacerbates myocardial oxidative stress and myocardial fibrosis. Silencing of PRR expression with short hairpin RNA (shRNA) technology reversed the myocardial damage mediated by PRR. Additionally, PRR activated phosphorylation of ERK1/2 and increased NOX4-derived reactive oxygen species and collagen expression in CFs with alcohol stimulation. Administration of the ERK kinase inhibitor (PD98059) significantly reduced NOX4 protein expression and collagen production, which indicated that PRR increases collagen production primarily through the PRR-ERK1/2-NOX4 pathway in CFs. In conclusion, our study demonstrated that PRR induces myocardial fibrosis and deteriorates cardiac function through ROS from the PRR-ERK1/2-NOX4 pathway during ACM development.